The monthly distribution & abundance of jellyfish (Medusae) species in the coastal waters of Penang National Park, Penang, Malaysia. - Yahya, Khairun (Universiti Sains Malaysia, 2012)
A study of monthly abundance and distribution of jellyfish population was conducted for 18-months period around the coastal waters of Penang National Park (PNP), Penang, Malaysia started November 2009 until April 2011. Towing and scooping methods were applied for samples collection using fishing boat cruising at the speed of approximately 2.5 nautical knots during neap tide. The scooping method used visual observation to detect jellyfish from the water surface.